A Framework for Maximizing Potential and Planning Career Success of The Millennial and Z Generation Workforce - Naufal, Irfan An; Fachrunnisa, Olivia (Universitas Muhammadiyah Surakarta, 2023)
This study aims to develop a framework to address the gap between the career expectations of the Millennial and Z Generation workforce and the perceived importance (priority) of their career success. This research was conducted by collecting data from 139 respondents from the Millennial Generation and Z Generation at one of the private and public universities in Semarang using a questionnaire method. The questionnaire contains questions about what the Millennial Workforce and Z Generation expect in choosing a career and what factors are their priorities in achieving career success. The data collected was then analyzed using the gap analysis technique to find the gap between the desired things in choosing a career and the priority considerations in choosing a job. The results show that the Millennial Workforce and Z Generation have extrinsic career expectations such as salary, rewards, employment contracts, and future career opportunities. At the same time, considering interests or priorities in choosing a job is intrinsic, such as potential development opportunities, work-life balance, and company culture. In order to close the gap, this research will propose a framework that contains action plans that various stakeholders can carry out. This framework is expected to help the Millennial and Z Generation workforce maximize their potential and navigate them to achieve career success.